2015
DOI: 10.1021/acs.langmuir.5b02713
|View full text |Cite
|
Sign up to set email alerts
|

Anisotropic Shear Viscosity of Photoaligned Liquid Crystal Confined in Submicrometer-to-Nanometer-Scale Gap Widths Revealed with Simultaneously Measured Molecular Orientation

Abstract: In the context of the use of liquid crystals (LCs) as lubricants and lubricant additives, this study investigates the anisotropic shear viscosity of LCs confined in nanometer-sized gap widths subject to both shearing and photoalignment. The photoalignment is achieved using anisotropically dimerized polyvinyl cinnamate (PVCi) films coated on substrates. We simultaneously measure the viscosity and order parameter of a liquid crystal (4-cyano-4'-pentylbiphenyl) confined and sheared in the gap range of 500 nm down… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 43 publications
0
13
0
Order By: Relevance
“…Outcome of this study will help researchers in rational designing of optical switchable windows, optical devices for telescope and other liquid crystal devices where efficiencies of devices are largely controlled by the orientational dynamics of the LCs molecules ,. Reorganization time of LCs molecules, obtained in this study, can be correlated with the response time of rearrangements of LCs molecules against an external electric/magnetic field in a birefringence LC cell . Optical studies using polarized microscope reveal different phases with distinct textures within LCs.…”
Section: Introductionmentioning
confidence: 79%
See 1 more Smart Citation
“…Outcome of this study will help researchers in rational designing of optical switchable windows, optical devices for telescope and other liquid crystal devices where efficiencies of devices are largely controlled by the orientational dynamics of the LCs molecules ,. Reorganization time of LCs molecules, obtained in this study, can be correlated with the response time of rearrangements of LCs molecules against an external electric/magnetic field in a birefringence LC cell . Optical studies using polarized microscope reveal different phases with distinct textures within LCs.…”
Section: Introductionmentioning
confidence: 79%
“…[1,[14][15][16] Reorganization time of LCs molecules, obtained in this study, can be correlated with the response time of rearrangements of LCs molecules against an external electric/magnetic field in a birefringence LC cell. [17][18][19] Optical studies using polarized microscope reveal different phases with distinct textures within LCs. Thermotropic LCs used in the present study exhibit several phases, namely: nematic, smectic and so on.…”
Section: Introductionmentioning
confidence: 99%
“…5CB liquid crystals have great solubility in common base oils because of their similar structure. It has been studied as a lubricant and additive, and shows good potential in reducing friction and externally controlling the lubricating performance [19]. Furthermore, 5CB molecules arrange in an orderly manner under the effect of surface adsorption [17,19] and flow alignment [12], which makes it an excellent model for studying the molecular orientation of the lubricant.…”
Section: Methodsmentioning
confidence: 99%
“…In the field of tribology, much attention has been focused on lubricants confined in nano-sized gaps. Itoh et al [19] studied the orientation parameter and viscosity of 5CB confined and sheared in a gap of size ranging from 500 nm to a few nm using a surface force apparatus (SFA). Zhang et al [20] explored the molecular orientation and friction performance of 5CB confined in the contact region with a gap size of tens of nanometers.…”
Section: Tflmentioning
confidence: 99%
“…Gao et al [21] reported that the adsorption of 5CB on the sliding steel surfaces play an important role in the friction reduction. Itoh et al [22] also found that the slip of the 5CB layers adjacent to the substrate leads to low friction and high load capacity.…”
Section: Introductionmentioning
confidence: 97%